Representation of politeness in tabe' speech of the people of Idampang village, Gantarang Keke sub-district, Bantaeng district: Representasi kesantunan tutur kata tabe' masyarakat desa idampang, kecamatan gantarang keke, kabupaten bantaeng - Kaharuddin; Sitti Hajar; Ridha Ichwanty Sabir; Andi Marwan (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2023)
Tabe” iis ian iexample iof iancestral icultural iheritage ior ilocal iwisdom iof ithe ipeople iof iSouth iSulawesi ito irespect ior irespect iother ipeople. i"Tabe" iis imost ioften iused iwhen iasking ipermission ito ipass iby ianother iperson. iThe i"Tabe" ibehavior iis ia isymbol iof irespecting iand irespecting ianyone iin iour ipresence. iThis iword icomes ifrom iSanskrit: ikşantavya ior iksantawya. iIn iSanskrit iit imeans i"sorry". iSince iMalays icannot ipronounce ithe isound i/v/, ithis isound ibecomes i/b/. iSo ithis iword iturns iinto iksantabya iand ifinally ibecomes isantabe iand ieven itabe ior itabik. iIn ia icertain isense, itabik ialso imeans ia irespectful igreeting i(Jan iGonda, i1973, iSanskrit iin iIndonesia, ipage i640 ionwards). iTabik iversions ifor ieach iplace, icity iand iregion iare ialso idifferent . his istudy iaims ito idetermine ithe ilevel iof iawareness iof ithe ipeople iof iGantarang ikeke iDistrict, iBantaeng iRegency itowards ithe imappatabe itradition iof ipracticing ithe isecond iprinciple iof iPancasila ito idetermine ithe ifactors ithat icause ithe icommunity iin iGantarang ikeke iDistrict, iBantaeng iRegency ito inot iimplement ithe imappatabe itradition. iThis itype iof iresearch iis ia iqualitative idescriptive istudy. iThe iinformants i iin ithis istudy iwere i13 ipeople iin ithe icommunity iin ithe iGantarang ikeke isub-district, ischool iteachers, icommunity ileaders iand ireligious ileaders, iwho iwere icarried iout ideliberately iwith icertain icriteria iusing ipurposive isampling itechnique. iData icollection iwas icarried iout iby imeans iof iinterviews, iobservation iand idocumentation. iThe iresults iof iresearch ion ipublic iawareness iin